Integrated Assessment of Kirala Kele Wetland Health: Bridging the Gap between Water Quality Parameters and Biotic Components - Aththanayake, A. M. N. S.; Nikawela, N. D. L.; Bellanthudawa, B. K. A.; Wijetunga, S. (Water science & technology. Water supply, 2024)
The present study was carried out to assess the health of the Kirala Kele Wetland, Sri Lanka, by coupling water quality indices and bioindicators. A total of 12 sampling sites were selected to represent different land-use patterns of the Kirala Kele Wetland using purposive sampling technique, and sampling was conducted from March 2021 to May 2021, on a monthly basis. Triplicated samples (n = 3) were obtained for each sampling event at each sampling site. Aquatic macroinvertebrates were collected from each site to determine the biological water quality using the Biological Monitoring Working Party (BMWP) score. Weighted Arithmetic Water Quality Index (WAWQI) was calculated to understand the physicochemical parameters of water, and the mean values of physicochemical water quality parameters were compared with the Sri Lankan water quality standards. According to the WAWQI for the different sampling sites, water is not suitable for drinking without treatment. The resulted BMWP score (BMWP = 61) shows that the water quality is acceptable (clean but slightly impacted) for biotic components of the wetland in accordance with the aquatic macroinvertebrates present. Spatial variation in water quality parameters and the aquatic macroinvertebrates were taken into account, and the temporal variation in water quality parameters within the 3 months from March to May was considered.